2011
DOI: 10.1063/1.3657502
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet printing of single-walled carbon nanotube thin-film transistors patterned by surface modification

Abstract: In this paper, we report a method for the inkjet printing of single-walled carbon nanotube thin-film transistors (SWCNT TFTs). Although inkjet technology is a powerful tool for the fabrication of SWCNT TFTs, the diameter of the ink droplets (100 μm) strictly limits the device size. Here, we surmount this limitation by combining inkjet technology and site-selective deposition based on the patterning of self-assembled monolayers. We have synthesized patterned SWCNT films with feature widths less than 100 μm usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…These results are comparable to values reported in the literature for printed CNT FETs (Supporting Information Figure S1). [19][20][21][22][23][24][25][26][27][28] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 The similarity in elemental composition to that of clothes afforded our elastomeric FET to possess clothes-like robustness and softness. To demonstrate this important point, our elastomeric FET was exposed to experiments spanning some of the most severe conditions of daily life.…”
mentioning
confidence: 87%
“…These results are comparable to values reported in the literature for printed CNT FETs (Supporting Information Figure S1). [19][20][21][22][23][24][25][26][27][28] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 The similarity in elemental composition to that of clothes afforded our elastomeric FET to possess clothes-like robustness and softness. To demonstrate this important point, our elastomeric FET was exposed to experiments spanning some of the most severe conditions of daily life.…”
mentioning
confidence: 87%
“…Several methods have been proposed to print CNTs by mixing into a solution, including painting [20], spraying [21], and inkjet printing [22]. Inkjet printing is a promising method to draw complex pattern conveniently, especially when a desktop inkjet printer is employed.…”
Section: Introductionmentioning
confidence: 99%
“…7 These techniques have attracted considerable attention as a fundamental processing technology in the emerging field of "printed electronics (PE)." [8][9][10][11][12][13][14][15][16] In PE, functional microdroplet inks that contain dissolved or dispersed semiconducting 17 or metallic materials 18 are deposited to manufacture active or passive electronic components. Several reports have demonstrated that predefined patterned surface-energy modification can be used to attain fine thin-film patterning for manufacturing PE circuits.…”
Section: Introductionmentioning
confidence: 99%